Pengaruh Pemasaran Media Sosial terhadap Keputusan Pembelian Somethinc di Kota Tangerang Selatan - Sabathini, Graciella; Nofiawaty, Nofiawaty; Putri, Yulia Hamdaini (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the effect of social media marketing on purchasing decisions at Somethinc in South Tangerang City. This study is quantitative research with a survey method. The sampling technique used is non-probability sampling towards society in South Tangerang City. Data was collected through a questionnaire via google form for 100 respondents. This research used simultaneous tests (F-test), partial tests (T-test), and multiple linear regression analysis. The results showed social media marketing has a significant effect on purchasing decisions. Content creation, connecting, and community building partially effect purchasing decisions. Content sharing partially has no effect on purchasing decisions. Connecting has a dominant influence on the purchasing decision of Something in South Tangerang City. Keywords: social media marketing, purchase decisions